Interactive effects of guilt and moral disengagement on bullying, defending and outsider behavior. Issue 4 (1st October 2016) - Mazzone, Angela; Camodeca, Marina; Salmivalli, Christina
Abstract: We examined the moderating effect of guilt on the associations between moral disengagement and bullying, defending and outsider behaviors in a sample of 404 students (203 boys; M age = 11.09 years; SD  = 1.48). Bullying, defending and outsider behavior were assessed through peer nominations, whereas guilt and moral disengagement were assessed by self-reports. Results showed that moral disengagement was associated with high levels of bullying and low levels of defending. Guilt was negatively associated with bullying and positively with defending. A moderating effect for guilt was also found: increasing levels of moral disengagement contributed to more bullying and outsider behavior, and to less defending, among students with low levels of guilt. The current research broadens the extant literature, showing the combined effects of guilt and moral disengagement on bullying-related behaviors.